PEMBERDAYAAN KELOMPOK IBU YANG MEMILIKI BALITA BERISIKO STUNTING DI BANJAR TRIWANGSA-PAYANGAN GIANYAR BALI - Ni Putu Diah Witari; Anak Agung Istri Aryastuti; Ni Wayan Rusni (UNHI Press, 2020)
Stunting is still a major nutritional problem in Indonesia and Bali. One district that has a fairly high stunting rate is Bresela Village, Payangan District. Triwangsa is one of the district located in Bresela village, based on a quick survey conducted on pregnant women and mothers who have babies under two years old in Triwangsa district, Bresela Village, Payangan, low knowledge and bad attitudes and behavior towards stunting prevention especially in terms of time, type and form of complementary feeding as a nutritional intake for the first 1000 days of life. The service implementation method is in the form of interactive dialogue and a demonstration of making balanced solid food. This activity succeeded in increasing partners' knowledge by 75% regarding stunting and balanced complementary foods of breast milk. After the assistance is carried out, it can be seen that the behavior changes of partners in providing balanced complementary foods to toddlers.